Organotin Complexes of 2-Substituted Benzimidazoles - Vyas, P.C.; Kaur, N.; Vyas, P.; Kaushal, A.K. (Asian Journal of Chemistry, 2010)
Some novel complexes of organo-tin derivatives with biologically important benzimidazoles have been synthesized and characterized on the basis of elemental analysis, ultraviolet and IR spectral studies. These derivatives were prepared by reacting R2SnX2 (where X = OR´, Cl; R and R´ = CH3, C2H5, C6H5) with 2-(o-hydroxy phenyl) benzimidazoles and 2-(o-amino phenyl) benzimidazoles in 1 : 2 and 1 : 1 molar ratios respectively in dry chloroform and benzene.